Online mindfulness-based intervention for women with pregnancy distress: design of a randomized controlled trial - Lianne P. Hulsbosch; Ivan Nyklíček; Eva S. Potharst; Margreet Meems; Myrthe G. B. M. Boekhorst; Victor J. M. Pop (BMC, 2020)
Abstract Background Psychological distress during pregnancy is common: up to 20% of the childbearing women experience symptoms of depression and anxiety. Apart from the adverse effects on the woman herself, pregnancy distress can negatively affect pregnancy outcomes, infant health, postpartum mother-child interaction and child development. Therefore, the development of interventions that reduce pregnancy distress is very important. Mindfulness-based interventions (MBIs) show promising positive effects on pregnancy distress, but there is a need for randomized controlled trials with sufficient power. Trials on online MBIs, which are readily accessible and not expensive, also show positive effects on stress reduction in non-pregnant populations. Moreover, specific working mechanisms of MBIs remain unclear. The aim of the current study is to test the effectiveness of an online MBI in pregnant women with pregnancy distress, as well as exploring potential working mechanisms. Methods The current study is a randomized controlled trial with repeated measures. Consenting women with elevated levels of pregnancy distress will be randomized into an intervention group (MBI) or control group (care as usual) around 12 weeks of pregnancy, with an intended sample size of 103 women in each group. The primary outcome, pregnancy distress, will be assessed via questionnaires at baseline, halfway through the intervention and post intervention in both intervention and control group, and after 8 weeks follow-up in the intervention group. Secondary outcomes are mindfulness skills, rumination and self-compassion, which are also seen as potential working mechanisms, and will be assessed via questionnaires before intervention, halfway through the intervention, post intervention and after 8 weeks follow-up in the intervention group. Tertiary outcome variables are obstetric data and will be collected from the obstetric records for both intervention and control group. Analyses will be based on the intention-to-treat principle. Multilevel regression models for repeated measures (mixed models) will be used to evaluate changes in primary and secondary outcome variables. Tertiary outcomes will be compared between groups using independent t-tests and Chi Square analyses. Discussion The trial is expected to increase knowledge about the effectiveness of online MBIs during pregnancy in women with pregnancy distress and to evaluate potential working mechanisms. Trial registration ClinicalTrials.gov: NCT03917745 , registered on 4 March 2019. Protocol Version 3.0., 20 February 2020.